Vertical integration between container lines and terminal operators : terminal operator’s perspective - Chang, Wan Jun. (2009)
Global terminal operators have become more influential in this emerging trend of port privatization. Currently, the top 20 global terminal operators handle 13% of the world container throughput, and by 2013, it is estimated to become 58%.